Implementasi Asesmen Diagnostik sebagai Dasar Perencanaan Pembelajaran Berdiferensiasi di SD Negeri 75 Kota Bengkulu - Putri Maysyah Della R; Yerin Anugrah; Heny Friantary; Susi Sales (MODELING: Jurnal Program Studi PGMI, 2026)
The implementation of the Kurikulum Merdeka (Independent Curriculum) positions diagnostic assessment as an initial step in designing instruction tailored to students' learning needs. This study aims to describe the implementation of diagnostic assessment as a basis for planning differentiated instruction at SD Negeri 75 Bengkulu City. The study employs a qualitative approach with a descriptive method. Research informants included the school principal, classroom teachers, and students. Data were collected through observation, in-depth interviews, documentation, and the review of instructional planning documents. Data analysis utilized the Miles, Huberman, and Saldaña model, comprising data condensation, data display, and conclusion drawing. The results indicate that teachers conducted diagnostic assessments covering both cognitive and non-cognitive aspects at the beginning of the semester and prior to introducing new material. The information obtained was used to map students' prior knowledge, learning styles, interests, characteristics, and learning needs. These mapping results served as the foundation for formulating learning objectives and teaching modules, as well as for devising strategies for differentiating content, processes, products, and the learning environment. Challenges encountered included time constraints, administrative burdens, and teachers' proficiency in developing comprehensive diagnostic assessment instruments. The school addressed these issues through learning communities, internal training, academic supervision, and teacher collaboration. The study concludes that the implementation of diagnostic assessment positively contributes to the effectiveness of differentiated instruction by ensuring that teaching is better aligned with students' characteristics.